(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2025)
This study analyzes the stabilization of the subgrade of the road between the communities of Teligote and Masabachos in Tungurahua, Ecuador, using lime and sodium chloride. The results show that lime increases the CBR by 150% and significantly reduces plasticity, while sodium chloride improves soil cohesion and strength, with a 120% increase in CBR. Both stabilizers are viable and effective, but lime excels in strength and durability. The pavement design based on these improvements ensures adequate infrastructure for the projected traffic. This study contributes to sustainable road development, enhancing connectivity and living conditions in rural communities, and offers a replicable model for similar projects in developing countries.